Hubungan Antara Maskulin Gender Role dengan Ekspresi Emosional pada Remaja Laki-Laki - Susan, Susan; Wahyu Endang Setyowati; Betie Febriana (Journal of Medical Practice and Research, 2025)
Adolescent males are in a crucial developmental phase and are faced with social norms known as the Masculine Gender Role. This gender role often demands men to display strength, resilience, and Restrictive Emotionality (the limitation of emotional expression). The pressure to refrain from expressing feelings excessively, as it is often perceived to diminish masculinity, can hinder their emotional development. In the context of nursing, understanding this relationship is important to support mental health and promote healthy emotional expression in adolescent males. Therefore, this study was conducted to analyze the relationship between masculine gender role and emotional expression in adolescent males. Method: The type of research used was quantitative research with a cross-sectional design. The subjects of the study were adolescent males at SMA Negeri 1 Sultan Agung Semarang. The sample size in this study was 304 respondents. The bivariate test used to analyze the relationship between variables was the Spearman Rank correlation analysis. Results: Based on the Spearman Rank correlation analysis, a correlation coefficient (r) of -0.968 was obtained with a significance value (p) of p < 0.01. This result indicates a very strong and significant negative relationship between masculine gender role and emotional expression in adolescent males